The Accountability and Transparency of Police Record Certificate (SKCK) Issuance Services at the Bali Regional Police - I Wayan Aditya Pradnyandita; Erikson Sihotang; Zuhro Nurindahwati (Return : Study of Management, Economic and Bussines, 2024)
The role of the Bali regional police in providing accountable and transparent police record certificate services is very large, measured by the best service quality indicators into 5 dimensions, including Tangible (tangible), Reliability (reliability), Responsiveness (responsiveness), Assurance (guarantee), and Empathy (empathy). The obstacles for the Bali Regional Police in issuing police record certificates for the Bali Regional Police are lack of facilities and infrastructure, lack of human resources or staff, and lack of public awareness. Efforts to overcome problems in improving the quality of services for making police record certificates in the Bali regional police intelligence and security unit are maximizing facilities and infrastructure, increasing human resources, providing socialization and evaluation.